Embryo and fetal pathology: Color atlas with ultrasound correlation - Barness, Enid Gilbert (Cambridge University, 2013)
Exhaustively illustrated in color with over 1000 slides, figures, and sonographs, this uniquely authoritative atlas provides the clinician with a visual guide to diagnosing congenital anomalies in every organ system in the human fetus. Gross pathologic findings are correlated with sonographic features to confirm visually the diagnoses for all organ systems. All practitioners of maternal-fetal medicine will find this atlas an invaluable resource.